Pengembangan Keterampilan Masyarakat melalui Transformasi Perpustakaan Berbasis Inklusi Sosial pada Perpusdes Lentera Desa Buluagung Karangan Trenggalek - Kamidah, Siti Nurul; Syafaah, Darisy (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2022)
Library as a place in developing community skills in order to do transformations that suitable for people need, one of them is for transform into libraries based on social inclusion. This research was done in order to describe about transforming of the village library